Archaeology, history, and predictive modeling research at Fort Polk, 1972-2002 - Anderson, David G., 1949- (Book collections on Project MUSE., 2003)
Fort Polk Military Reservation encompasses approximately 139,000 acres in western Louisiana 40 miles southwest of Alexandria. As a result of federal mandates for cultural resource investigation, more archaeological work has been undertaken there, beginning in the 1970s, than has occurred at any other comparably sized area in Louisiana or at most other localities in the southeastern United States. The extensive program of survey, excavation, testing, and large-scale data and artifact recovery, as well as historic and archival research, has yielded a massive amount of information. While superbly.